ANALISIS EVOLUSI DAN TRANSFORMASI TEKNOLOGI BLOCKCHAIN DALAM ARSITEKTUR SISTEM INFORMASI GLOBAL: TANTANGAN, KEAMANAN, DAN IMPLEMENTASI LINTAS SEKTOR - Rizky Gilang Ramadani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Blockchain technology has evolved significantly from a cryptocurrency transaction platform into a strategic technology that supports the transformation of global information system architectures. Its core characteristics, including decentralization, transparency, security, and data integrity, have made blockchain an innovative solution for improving efficiency, reliability, and secure information exchange across various sectors. This study aims to analyze the evolution of blockchain technology, identify implementation challenges, evaluate security aspects, and examine its applications in finance, healthcare, education, government, supply chain management, and the Internet of Things (IoT). The research employs a literature review approach by examining relevant scientific journal articles, conference proceedings, books, and other academic publications related to blockchain technology. The collected data were analyzed descriptively through identification, classification, synthesis, and interpretation of previous research findings. The results indicate that blockchain has evolved from Blockchain 1.0, which primarily focused on cryptocurrency, to Blockchain 4.0, integrating Artificial Intelligence (AI), the Internet of Things (IoT), cloud computing, and other emerging digital technologies. Blockchain implementation has demonstrated significant benefits in enhancing data security, transaction transparency, operational efficiency, and stakeholder trust. Nevertheless, several challenges remain, including scalability, interoperability, regulatory issues, energy consumption, and the availability of skilled human resources. Therefore, stronger collaboration among governments, industries, academic institutions, and technology developers is essential to maximize blockchain implementation in supporting the transformation of global information system architectures.